A roadmap for ladybird conservation and recovery - Soares, António O; Haelewaters, Danny; Ameixa, Olga M C C; Borges, Isabel; Brown, Peter M J; Cardoso, Pedro; de Groot, Michiel D; Evans, Edward W; Grez, Audrey A; Hochkirch, Axel; Holecová, Milada; Honěk, Alois; et al. (Conservation biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short-term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non-native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid-term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management-intensity gradient. Long-term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.
Keywords: 生态威胁; tendencias temporales y espaciales; 瓢虫科; Population Dynamics; acciones en escala de tiempo a corto, amenazas, mediano y largo plazo; temporal and spatial trends; Coccinellidae; Ecosystem; guia para la conservación; zvířata; ecological threats; roadmap to conservation; populační dynamika; 保护路线图; ecosystem services; Endangered Species; 生态系统服务; 短期、中期和长期时间尺度的行动; zachování přírodních zdrojů; Conservation of Natural Resources; 时空趋势; short-, mid-, and long-term timescale actions; ohrožené druhy; Animals; servicios ecosistémicos; ekosystém